Distinct associations of complement C3a and its precursor C3 with atherosclerosis and cardiovascular disease - Hertle, Elisabeth; van Greevenbroek, Marleen M.; Arts, Ilja C.; van der Kallen, Carla J.; Geijselaers, Stefan L.; Feskens, Edith J.; Jansen, Eugene H.; Schalkwijk, Casper G.; Stehouwer, Coen D. (Thrombosis and Haemostasis, 2014)
Complement C3 is a novel risk factor for cardiovascular disease (CVD), but the underlying mechanism is currently unknown. We determined the associations of the anaphylatoxin C3a, the activation product of C3, and of C3 itself with estimates of atherosclerosis and CVD. We studied associations of C3a and C3 with carotid intima-media thickness (cIMT), ankle-arm blood pressure index (AAIx) and CVD in cross-sectional analyses among 545 participants of the Cohort on Diabetes and Atherosclerosis Maastricht (CODAM) study (62% men, 59.4 ± 6.9 years) and examined effect modification by smoking. We conducted linear and logistic regression analyses with adjustments for age, sex, glucose metabolism status, lipids, adiposity, renal function, blood pressure, pack-years smoked, physical activity, use of medication and investigated mediation by inflammation. C3a was independently associated with cIMT (β=0.032 mm, [95% confidence interval: 0.004; 0.060]) and AAIx (β=−0.022, [−0.043; −0.001]), but C3 was not. Effect modification by smoking was only observed for CVD (Psmoking*C3a=0.008, Psmoking*C3=0.018), therefore these associations were stratified for smoking behaviour. Both C3a (odds ratio [OR] =2.96, [1.15; 7.62]) and C3 (OR =1.98, [1.21; 3.22]) were independently associated with CVD in heavy smokers. The association of C3 with CVD was independent of C3a. Low-grade inflammation did partially explain the association of C3a with AAIx, but not the other observed associations. This suggests that C3a and C3 have distinct roles in pathways leading to CVD. C3a may promote atherosclerosis and additionally advance CVD in heavy smokers. Conversely, C3 may be associated with CVD in heavy smokers via pathways other than atherosclerosis.
Keywords: Complement; C3; C3a; atherosclerosis; cardiovascular disease